Eculizumab epitope on complement C5: Progress towards a better understanding of the mechanism of action. (September 2016) - Brachet, Guillaume; Bourquard, Thomas; Gallay, Nathalie; Reiter, Eric; Gouilleux-Gruart, Valérie; Poupon, Anne; Watier, Hervé
Highlights: An in silico docking method was applied to determine the epitope of eculizumab on complement C5. The discontinuous nature of the epitope was confirmed by a peptide binding assay. The species specificity of eculizumab is due to Trp917, an aminoacid outside the known epitope. Abstract: Eculizumab is an anti-complement C5 monoclonal antibody which has greatly improved the prognosis and outcomes of nocturnal paroxysmal hemoglobinuria and atypical hemolytic and uremic syndromes. It is also known to be very species-specific for human C5, despite an important degree of conservation of the targeted macroglobulin domain, MG7, with that of other primates. However, the published eculizumab linear epitope does not explain this species specificity. Sequence analysis, in silico docking and reverse phase protein array were implemented to fully characterize the eculizumab epitope on human complement C5. Several residues potentially involved in the species specificity were identified outside the known epitope by sequence analysis. In silico docking confirmed the implication of a beta-hairpin located between residues 913 and 922, outside the known epitope, in the binding of eculizumab to C5. This beta-hairpin spreads from S913 to I922 and contains a tryptophan residue on position 917 which is unique to humans. The contribution of both this peptide and the already known one epitope, which spreads between residues C883 and S891, was validated by reverse phase protein assay, clearly demonstrating the discontinuous nature of the epitope. Two residues in particular, Arg885 and Trp917, were defined as major participants in the interaction of C5 and eculizumab. Their important role was confirmed by the recent publication of a crystal structure of eculizumab Fab bound to C5. The beta-hairpin not only explains the fine species specificity of eculizumab but is also an important site at the C5/C5 convertase interface, revealing how eculizumab acts as a competitor of C5 convertases.